Combining Incompatible Processes for Deracemization of a Praziquantel Derivative under Flow Conditions. Issue 10 (19th January 2021) - Valenti, Giulio; Tinnemans, Paul; Baglai, Iaroslav; Noorduin, Willem L.; Kaptein, Bernard; Leeman, Michel; ter Horst, Joop H.; Kellogg, Richard M.
Abstract: An efficient deracemization method for conversion of the racemate to the desirable ( R )‐enantiomer of Praziquantel has been developed by coupling incompatible racemization and crystallization processes. By a library approach, a derivative that crystallizes as a conglomerate has been identified. Racemization occurs via reversible hydrogenation over a palladium on carbon (Pd/C) packed column at 130 °C, whereas deracemization is achieved by alternating crystal growth/dissolution steps with temperature cycling between 5–15 °C. These incompatible processes are combined by means of a flow system resulting in complete deracemization of the solid phase to the desired ( R )‐enantiomer (98 % ee ). Such an unprecedented deracemization by a decoupled crystallization/racemization approach can readily be turned into a practical process and opens new opportunities for the development of essential enantiomerically pure building blocks that require harsh methods for racemization. Abstract : The ( R ) enantiomer of Praziquantel is more active against schistosomiasis (bilharzia, snail fever). The cheaper, commonly used, racemate can be deracemized via a conglomerate derivative to this enantiomer, which is obtained in 98 % ee using a flow system in which Pd‐catalyzed high‐temperature racemization is coupled to low‐temperature cycled crystallization.